An Analysis of Gen Z’s Digital Slang: Patterns from TikTok Comment Sections - Susana Hamu Eti; Rosalinah, Yanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The digital communication landscape has undergone a profound transformation, with social media platforms like TikTok emerging as critical sites for linguistic innovation. This research examines the intricate mechanisms of digital slang generation among Generation Z, exploring the complex interplay between technological architecture, user creativity, and sociocultural dynamics. Employing a qualitative content analysis approach, the study investigates linguistic practices within TikTok comment sections, focusing on slang formation mechanisms, algorithmic dissemination, and cultural identity functions. The research reveals sophisticated linguistic strategies including zeroidation, diphthongization, lexical shifts, and code-mixing, demonstrating how Gen Z actively reconstructs communication paradigms. The platform's algorithmic recommendation system facilitates unprecedented rapid language evolution, with slang terms transitioning from marginal usage to widespread adoption within hours. Digital slang serves multifaceted purposes: creating humor, signaling contemporaneity, facilitating social relations, and establishing intimate group identities. The study highlights the tension between linguistic innovation and preservation, suggesting that digital platforms are not passive mediums but active agents in linguistic transformation. By providing a nuanced sociolinguistic lens, the research contributes crucial insights into how digital technologies reshape communicative landscapes and generational identity construction in the 21st century. Keywords: Digital Slang, Gen Z, TikTok, Linguistic Innovation, Social Media Communication